The Interplay of Malagasy Cultural Values and Quality Assurance within an Ecclesial Setting: A Case Study of the Tranovato Ambatonakanga Temple, Antananarivo - Rakotomavo Emmanuel Andriamanantsalama; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR-Publisher), 2024)
This article examines the challenges, opportunities, and potential conflicts related with implementing a quality culture within a Malagasy ecclesial context, using the FJKM Tranovato Ambatonakanga Protestant Temple in Antananarivo as a case study. The study explores the inherent tensions between Malagasy cultural values, particularly Fihavanana (community spirit), Moramora (taking things easy/going slowly), and Hena-maso (respect for hierarchy/avoiding direct confrontation), which remain deeply ingrained in Malagasy society, and the demands of modern management practices emphasizing rigor, standardization, and continuous improvement. Malagasy culture's emphasis on consensus, solidarity, and tolerance can pose challenges to the adoption of structured, standardized processes characteristic of quality management systems. Furthermore, the often-informal nature of church management structures can complicate the strict application of quality theory principles and regulations. However, congruences between certain Christian values, such as commitment, truthfulness, and righteousness, and core quality principles offer potential avenues for the gradual integration of quality management within a religious setting. Employing a mixed-methods approach, combining both qualitative and quantitative data collection, the study analyzes the perceptions and practices of temple stakeholders, exploring the interrelationships between the variables under investigation. The findings underscore the importance of adapting, and even indigenizing, quality culture to the specific ecclesial context and local realities to mitigate resistance and foster greater acceptance. The article concludes that successful implementation of a quality approach within an ecclesiastical environment necessitates a contextually sensitive and pedagogically informed strategy, one that respects traditional values while simultaneously promoting the improvement of existing practices.